1997
DOI: 10.1016/s1010-7940(97)84614-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of time to discharge following coronary artery by pass grafting

Abstract: A large number of pre- and postoperative factors are associated with an increased time between operation and time to discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…On the other hand, the average length of stay for non‐infected patients who underwent CABG surgery in the present study was 7.8 days. This result is also consistent with the figures reported in different studies in USA, Canada and UK 30,34 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, the average length of stay for non‐infected patients who underwent CABG surgery in the present study was 7.8 days. This result is also consistent with the figures reported in different studies in USA, Canada and UK 30,34 …”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results of this study showed that the length of stay in the hospital for infected patients was twice the length of stay for non‐infected patients. The average length of stay in the hospital for infected patients in this study was 16.7 days; This result is consistent with previous studies 7,9,30,34 . On the other hand, the average length of stay for non‐infected patients who underwent CABG surgery in the present study was 7.8 days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in accord with studies that have examined the impact of BMI on hospital outcomes among patients with general medical conditions, 15 those with recent trauma, 16,17 and those requiring intensive care. 18,19 Extended length of hospital stay has been consistently shown to be associated with obesity, 15,20,21 and even though one study found this difference between the highest and lower categories of BMI to be only 1 day, such a delay may have financial and psychological implications, and expose patients to the additional risk of acquiring nosocomial conditions. 15 The BMI groups did not differ in presenting stroke severity; therefore, the differences in short-term outcome must be due to other factors such as a more frequent occurrence of in-hospital complications or longer recovery time.…”
Section: Commentmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia occurring after coronary artery bypass graft (CABG) surgery and results in increased morbidity and prolonged post-operative hospital stay with a resultant increase in healthcare costs [1][2][3][4][5][6][7]. AF following minimally invasive coronary artery bypass surgery is analogous to AF after CABG, with a similar possibility for associated comorbidities and increases in healthcare costs [8].…”
Section: Introductionmentioning
confidence: 99%